Organization of breastfeeding in neonatal intensive care units: discussion issues - Irina A. Belyaeva; Leyla S. Namazova-Baranova; Nikolai N. Volodin; Elena E. Petryaykina (Union of pediatricians of Russia, 2019)
The priority of breastfeeding in the care of premature infants is not in doubt. For preterm babies, breastfeeding provides a dual effect, reducing the risk of both immediate and long-term effects associated with prematurity. In this regard, extraordinary efforts are being made at the international level to promote and support breast-feeding of newborns, including in intensive care units. Mother's own milk is the first choice for feeding a premature baby. In recent years, the problems of quality and safety of expressed breast milk - both pasteurized and fresh - for newborn patients of intensive care units are discussed. The authors point out that the treatment procedures and storage conditions of expressed breast milk differ significantly; there are no common criteria for its microbiological safety, which limits the use of this unique product, especially in premature infants. In addition to the risk of bacterial infection, the risk of infection with cytomegalovirus (CMV) when using fresh milk from a CMV - seropositive mother is discussed for premature infants. The review examines the criteria for the risk of CMV infection in children and indications for selective treatment of breast milk for inactivation of a probable pathogen.